Fli1 Downregulation in Scleroderma Myeloid Cells Has Profibrotic and Proinflammatory Effects - Bujor, Andreea M.; El Adili, Fatima; Parvez, Arshi; Marden, Grace; Trojanowska, Maria (Frontiers in Immunology, 2020)
Scleroderma is an autoimmune connective tissue disease characterized by immune dysregulation, vasculopathy and fibrosis. We have previously demonstrated that low Fli1 expression in scleroderma fibroblasts and endothelial cells plays an important role in SSc pathogenesis. Cells of myeloid and lymphoid origin also express Fli1 and are dysregulated in patients with SSc, playing key roles in disease pathogenesis However, a role for immune Fli1 in SSc has not yet been described. Our aim was to elucidate whether Fli1 contributes to the immune dysregulation seen in scleroderma. Comparison of the expression of Fli1 in monocytes, B- and T-cell fractions of PBMCs isolated from scleroderma patients and healthy controls, showed an increase in Fli1 levels in monocytes. We used siRNA transfected human myeloid cells and mouse peritoneal macrophages obtained from Fli1flox/floxLysMCre+/+ mice, and found that markers of alternative macrophage activation were increased with Fli1 deletion. Coculture of Fli1-deficient myeloid cells and primary human or mouse fibroblasts resulted in a potent induction of collagen type I, independent of TGFβ upregulation. We next analyzed global gene expression profile in response to Fli1 downregulation, to gain further insight into the molecular mechanisms of this process and to identify differentially expressed genes in myeloid cells. Of relevance to SSc, the top most upregulated pathways were hallmark IFN-ɣ and IFN-α response. Additionally, several genes previously linked to SSc pathogenesis and fibrosis in general were also induced, including MCP-1, MCP-3, MMP12, and CXCL10. ANKRD1, a profibrotic transcription co-regulator was the top upregulated gene in our array. Our results show that Fli1-deficient myeloid cells share key features with cells from SSc patients, with higher expression of profibrotic markers and activation of interferon responsive genes, thus suggesting that low Fli1 may contribute to SSc pathogenesis.